Primary Pericardial Mesothelioma: A Rare Entity - Mohit Godar; Jianhua Liu; Pengguo Zhang; Yang Xia; Qinghai Yuan (Case Reports in Oncological Medicine)
Primary pericardial malignant mesothelioma is an extremely rare neoplasm that arises from the pericardial mesothelial cell layers. Clinical symptoms and signs are frequently nonspecific, and the diagnosis is usually made after surgery or at autopsy. There is no standard treatment for pericardial mesothelioma; nonetheless, radical surgery is the mainstay of therapy for localized disease. The neoplasm is highly aggressive and carries a dismal prognosis with an overall survival of less than six months. This paper presents a case study of a 68-year-old patient with a primary pericardial malignant mesothelioma. Radiologic evaluation revealed a small nodule in the posterior pericardium with pericardial and bilateral pleural effusions. The diagnosis was established after surgery by histological and immunohistochemical studies. The patient remained alive and free of disease for about 24 months; however, due to rapid local recurrence, the patient died 27 months after the surgical treatment.